2000
DOI: 10.1128/jvi.74.14.6680-6683.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Impedes the Establishment of Herpes Simplex Virus Type 1 Latent Infection but Has No Impact on Its Maintenance or Reactivation in Mice

Abstract: Murine models of gamma interferon (IFN-␥

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…To our knowledge, this is the first direct demonstration that IFN-␥ can block HSV-1 reactivation from latency in neurons. In vivo studies comparing wild-type and IFN-␥ knockout (GKO) mice on a BALB/c background demonstrated more rapid reactivation of HSV-1 from latency following induction by hyperthermic stress (3) or UV-B corneal irradiation (14) in GKO mice. In the former study the overall incidence of reactivation was also increased in IFN-␥-deficient mice, whereas this difference was not observed in the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first direct demonstration that IFN-␥ can block HSV-1 reactivation from latency in neurons. In vivo studies comparing wild-type and IFN-␥ knockout (GKO) mice on a BALB/c background demonstrated more rapid reactivation of HSV-1 from latency following induction by hyperthermic stress (3) or UV-B corneal irradiation (14) in GKO mice. In the former study the overall incidence of reactivation was also increased in IFN-␥-deficient mice, whereas this difference was not observed in the latter study.…”
Section: Discussionmentioning
confidence: 99%
“…Although PMNs are one of the initial cells that traffic to the cornea [3], CD4 + and CD8 + T lymphocytes are thought to be key components in the development of lesions associated with herpetic stromal keratitis [4][5][6][7]. Th2 cytokines exacerbate HSV-1 infection whereas Th1 cytokines are principally produced by those cells infiltrating the infected tissue and contribute towards resistance to virus replication and spread [8][9][10]. Chemokines expressed locally are likely involved in the recruitment of leukocytes into the site of infection with CCL2 and CXCL10 expressed or up-regulated significantly within the first 36 hr post infection relative to other chemokines including CCL3, CCL5, CXCL1, and CXCL9 [11].…”
Section: Introductionmentioning
confidence: 99%
“…"True" latent HSV-1 infections in humans and in animal models, including mice, have been extensively studied, and the need for immune cells and cytokines-in particular IFN-␥-was postulated (6,12,13,27,31,45,49). Latent HSV-1 infections have three separable phases: establishment, maintenance, and reactivation.…”
Section: Nk Cells or Mature T And B Cells Are Not Required To Resist mentioning
confidence: 99%